Current status of bacterial leaf blight in Malaysian rice plants - Mohd Din, Bibi Nazihah; Syd Ali, Nusaibah; Tan, Geok Hun; Yusop, Mohd Rafii (Gayathri Ashokkumar, 2023)
Bacterial leaf blight (BLB) of rice is among the most devastating pathosystem of rice in nearly all the rice-growing localities in tropical and temperate regions. In Malaysia, the disease was initially detected in paddy fields of Peninsular Malaysia in 1967, with yield losses reaching 70. Devastating BLB spread was in 2013 at Sekinchan, Selangor with 80 infection involving varieties of MR220, CL2, MR263 and MR 269, while at Northwest Selangor, 40 of the planting area involved MR284, MR220, CL2 and MR219 varieties. The country produced 71 of the rice after the Second National Agriculture Policy (NAP) in the year 2000 and only increased by 72 at the end of 2010, passing the target of 65 of SSL. Malaysia announced its intention to reach self-sufficiency level (SSL) by the year 2020, but has been extended to the year 2050. In general, several factors favour the BLB diseases development, particularly in irrigated and rainfed lowland areas, with temperatures of 25-34ºC and humidity above 70 instead of high nitrogen levels and absence of resistant varieties. This disease could be overcome through practising a few control methods to prevent the diseases development.